Pengaruh Motivasi Kerja terhadap Komitmen Afektif dengan Mediasi Stres Kerja pada Tenaga Kesehatan di RS Bhayangkara Mamuju - Sri Rizky Y Djuraedjo; Saparuddin Latu; Syamsuriyati Syamsuriyati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Low employee retention and high workloads among healthcare workers in hospitals can lead to decreased affective commitment to the organization. Work stress is a critical factor that weakens healthcare workers’ emotional attachment to their workplace, while work motivation is often considered essential for improving performance and employee loyalty. This study aims to analyze the effect of work motivation on affective commitment mediated by work stress among healthcare workers at Bhayangkara Hospital, Mamuju. This research employed a quantitative approach using an associative research design. The study was conducted at Bhayangkara Hospital Mamuju, with healthcare workers as the research respondents. A total of 97 respondents were selected using a total sampling technique. Data were collected through Likert-scale questionnaires and analyzed using SmartPLS software with the Structural Equation Modeling (SEM) method. The results indicate that work motivation does not have a direct effect on affective commitment. However, work motivation has a significant effect on reducing work stress, and lower work stress significantly increases affective commitment. Furthermore, work stress fully mediates the relationship between work motivation and affective commitment, indicating that improvements in motivation will only enhance affective commitment when accompanied by reduced work stress. These findings imply that hospital management should integrate motivational strategies with effective work stress management to strengthen healthcare workers’ affective commitment to the organization.